2011
DOI: 10.4049/jimmunol.1003879
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL/DR5 Plays a Critical Role in NK Cell-Mediated Negative Regulation of Dendritic Cell Cross-Priming of T Cells

Abstract: DCs are critical in initiating immune responses by cross-priming of tumor antigens to T cells. Previous results showed that NK cells inhibited DC-mediated cross-presentation of tumor Ags both in vivo and in vitro. In this study, enhanced Ag presentation was observed in draining lymph nodes in TRAIL−/− and DR5−/− mice compared to that of wild-type mice. NK cells inhibit DC cross-priming of tumor antigens in vitro, but not direct presentation of endogenous antigens. NK cells lacking TRAIL but not perforin were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
1
18
0
1
Order By: Relevance
“…Although IL-6 may stimulate NK-cell-mediated killing of cancer cells, IL-6 is also known as an autocrine stimulator of cervical neoplastic cell growth [35]. IL- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-6 may stimulate NK-cell-mediated killing of cancer cells, IL-6 is also known as an autocrine stimulator of cervical neoplastic cell growth [35]. IL- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some articles suggest that these cytokines and cytokine receptors can modulate the tumor microenvironment promoting the pathogenesis of cancer. [40][41][42][43][44] Therefore, for CC patients in the high-risk group these genes may reflect a changing TIME, which may contribute to CC progression and a poorer prognosis. There were significant differences in survival curves between patients with high-risk and low-risk scores.…”
Section: The Prognostic Value Of This Signaturementioning
confidence: 99%
“…Mechanistically, TRAIL + T cells appear to inhibit the proliferation of other alloreactive T cells. While a body of evidence suggests a role for the TRAIL/DR5 pathway in immune regulation (15,20), its physiological role in suppressing GVHD has not been clear (11). We found that TRAIL receptor DR5 expression is induced in APCs postirradiation and that GVHD suppression by TRAIL + T cells is less effective in DR5 KO recipients, suggesting that DR5 expression (possibly on host APCs) could play a role in GVHD suppression by TRAIL + T cells.…”
Section: Discussionmentioning
confidence: 56%